2019
DOI: 10.22559/folklor.979
|View full text |Cite
|
Sign up to set email alerts
|

İlköğretim Matematik Öğretmen Adaylarının Akademik Başarılarını Öğrenme Stilleri

Abstract: Bu çalışmada, ilköğretim matematik öğretmen adaylarının türev konusundaki akademik başarılarının öğrenme stillerine göre incelemesi amaçlanmıştır. Çalışmada genel tarama modeli kullanılmıştır. Çalışmanın örneklemini, 2015-2016 eğitim-öğretim döneminde Buca Eğitim Fakültesi İlköğretim Matematik Öğretmenliği Anabilim Dalı'nda öğrenim gören %75,86'sı (n=154) kadın, %24,14'ü (n=49) erkek olmak üzere toplam 203 öğretmen adayı oluşturmaktadır. Araştırmada veri toplama aracı olarak, öğretmen adaylarının türev kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The finding that field education courses for the profession should be increased is also found in the literature (Cetin et al, 2021;Demir et al, 2021). Both teacher groups emphasize that increased practice and more lectures by pre-service teachers would enhance their PCK (Aslan & Saglam, 2018;Basturk, 2009Basturk, , 2010Cetin et al, 2021;Eraslan, 2009;Uzun & Koparan, 2021). Specifically, teachers enrolled in the school experience course believe that the current time allocated to teaching practices is insufficient and advocate for additional practice opportunities, suggesting a transition from one semester of practice to two.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 67%
See 2 more Smart Citations
“…The finding that field education courses for the profession should be increased is also found in the literature (Cetin et al, 2021;Demir et al, 2021). Both teacher groups emphasize that increased practice and more lectures by pre-service teachers would enhance their PCK (Aslan & Saglam, 2018;Basturk, 2009Basturk, , 2010Cetin et al, 2021;Eraslan, 2009;Uzun & Koparan, 2021). Specifically, teachers enrolled in the school experience course believe that the current time allocated to teaching practices is insufficient and advocate for additional practice opportunities, suggesting a transition from one semester of practice to two.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 67%
“…Researchers recommend an extension beyond one year for an enriched practical experience. Utilization of teaching materials is advocated as a means to enhance lesson engagement, while pre-lesson preparation significantly contributes to the development of pre-service teachers (Aslan & Saglam, 2018;Basturk, 2010;Budak et al, 2011;Eraslan, 2009;Kocak et al, 2020). These studies reveal pre-service teachers' expectations from mentor teachers to be objective, serve as role models, offer guidance, provide feedback on lesson plans, and collaborate in the teaching process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another finding obtained in the research is that the learning styles of prospective teachers do not differ according to their gender. Altun and Yılmaz (2016) could not find a significant difference between learning styles and gender in their research with mathematics pre-service teachers. Similarly, Özsoy, Yağdıran and Öztürk ( 2004) conducted a research with 2ndary education students and found that there was no statistically significant relationship between learning styles and gender in their research.…”
Section: Discussionmentioning
confidence: 79%
“…In school practice it can be focused on these four points: planning, data collection, intervention and enrichment stages (Cansoy & Parlar, 2017). Altun (2020) found that teachers are motivated to develop, their selfawareness and their ability to collaborate develop in the study in which he examined the professional learning communities in two schools in action research. Aykan & Yıldırım (2021) reported that science teachers' pedagogical knowledge and content knowledge improved in their research in which they integrated the lesson study model into distance STEM education.…”
mentioning
confidence: 99%